PREDIKSI KESTABILAN SUHU PADA BABY INCUBATOR MENGGUNAKAN ALGORITMA BACKPROPAGATION - Hardiyanti Putri, Stefani; Winora, Okfa; Sukmawati, Yofa (Tekompedia : Jurnal Ilmiah Ilmu Komputer, 2024)
To maintain the quality of a medical device, an activity called calibration is carried out. Baby Incubator is a tool that functions to maintain the life of premature babies or have low birth weight (LBW), by maintaining temperature and humidity stability. The accuracy and precision of controlling the temperature and humidity in the baby incubator room is the main thing in maintaining the baby's condition in order to survive. If there is a failure or error in the system related to these two things, things will happen that can threaten the safety of babies who are being treated with baby incubators. Data processing using the Backpropagation algorithm through several stages, namely the initialization stage, activation stage, changing the weights from the input layer to the hidden layer, changing the weights of the hidden layer to the output layer, and the iteration stage. The accuracy and precision of the tool that the author makes is quite good because the sensors used have a high level of accuracy and precision.